Acupuncture and related techniques for obesity and cardiovascular risk factors: a systematic review and meta-regression analysis. Issue 4 (August 2020) - Chen, Jianrong; Chen, Dongping; Ren, Qing; Zhu, Weifeng; Xu, Sheng; Lu, Ling; Chen, Xiaofan; Yan, Dongmei; Nie, Heyun; Zhou, Xu
Objective: To assess how acupuncture and related techniques affect weight-related indicators and cardiovascular risk factors compared with non-acupuncture interventions in overweight and obese patients. Methods: We searched PubMed, Embase and CENTRAL up to 19 April 2018 and included relevant randomised controlled trials (RCTs). Weighted mean differences (WMDs) and 95% confidence intervals (CI) were pooled using the inverse variance method with random-effects model. Prespecified hypotheses were tested in meta-regression to investigate the source of heterogeneity. Statistical software packages used were RevMan 5.3.5 and Stata 14.0. Results: Thirty-three RCTs were included (n=2503 patients). Compared with non-acupuncture interventions, acupuncture produced a greater reduction in body weight (WMD −1.76 kg, 95% CI −2.22 to −1.30, I 2 =77%; moderate quality), body mass index (WMD −1.13 kg/m 2, 95% CI −1.38 to −0.88, I 2 =85%; low quality) and waist circumference (WMD −2.42 cm, 95% CI −3.22 to −1.62, I 2 =75%; moderate quality). Acupuncture plus lifestyle intervention resulted in a greater reduction in body weight than acupuncture alone (MD −1.94 kg, 95% CI −3.17 to −0.70). Acupuncture also led to a greater reduction in total cholesterol (WMD −12.87 mg/dL, 95% CI −22.17 to −3.57, I 2 =87%; very low quality) and low-density lipoprotein cholesterol (WMD −13.52 mg/dL, 95% CI −21.47 to −5.58, I 2 =74%; low quality). The differences were not statistically significant for blood glucose or blood pressure. Conclusion: In the short term, acupuncture and related techniques may produce a small but statistically significant degree of weight loss based on moderate- to low-quality evidence, and improve serum lipid parameters based on low- to very-low-quality evidence. Their effects on blood glucose and blood pressure remain uncertain.